Barrett Esophagus Length, Nodularity, and Low-grade Dysplasia are Predictive of Progression to Esophageal Adenocarcinoma. Issue 5 (May 2019) - Solanky, Dipesh; Krishnamoorthi, Rajesh; Crews, Nicholas; Johnson, Michele; Wang, Kenneth; Wolfsen, Herbert; Fleischer, David; Ramirez, Francisco C.; Katzka, David; Buttar, Navtej; Iyer, Prasad G.
Abstract : Goals: To investigate factors predictive of progression from nondysplastic Barrett esophagus (NDBE) or low-grade dysplasia (LGD) to high-grade dysplasia (HGD) or esophageal adenocarcinoma (EAC) using a large, prospective cohort of patients, wherein all esophageal biopsies undergo expert gastrointestinal pathologist review. Background: Efficacy and cost-effectiveness of endoscopic surveillance to detect incident EAC in the setting of Barrett esophagus (BE), particularly in NDBE patients, is questioned. Previous studies have reported factors predictive of progression to EAC to guide surveillance intervals, but their strength is limited by small sample size and absence of expert gastrointestinal pathologist involvement in esophageal biopsy review. Study: NDBE and LGD subjects were identified from a prospective registry in a tertiary care center. "Progressors" were BE subjects who developed HGD/EAC>12 months after the initial NDBE or LGD diagnosis. Cox proportional hazards model were used to identify predictors of progression. Results: In total, 318 with NDBE and 301 with BE-LGD (mean age, 62.6 y, 85% male) were included. The mean follow-up was 5.3 years. The 7 NDBE and 21 LGD subjects progressed to HGD/EAC. BE length [hazards ratio (HR), 1.16; 95% confidence interval (CI), 1.03-1.29], presence of nodularity (HR, 4.98; 95% CI, 1.80-11.7), and baseline LGD (HR, 2.57; 95% CI, 1.13-6.57) were significant predictors of progression on multivariate analysis. Conclusions: In this well-defined cohort of NDBE and BE-LGD subjects, BE length, presence of LGD, and nodularity were independent predictors of progression to HGD/EAC. These factors may aid in identifying high-risk patients who may benefit from closer endoscopic surveillance/therapy.